UPAYA PENERAPAN MEDIA YOUTUBE DALAM PENINGKATAN KETERAMPILAN MENYIMAK UNSUR CERITA LISAN - Nugroho, Syafrudin (sarasvati, 2020)
It is motivated by a corona pandemic that makes students study at home and their low ability to listen to elementary students. This study attempts to describe the improvement of listening skills in identifying verbal stories through YouTube. The research method used is descriptive qualitative. The study was conducted at Muhammadiyah Karangharjo Elementary School with a sample of grade III students totaling 27 students. The results of this study, an increase in students' listening skills using Youtube media.